Industry 4.0 in shipping: Implications to seafarers' skills and training. (March 2022) - Baum-Talmor, Polina; Kitada, Momoko
Highlights: The current discourse in Industry 4.0 in shipping tends to focus on technology-centred approaches, which are the limitations in effective adaptation to Industry 4.0. Human-centred approaches, including seafarers' career development, should be considered when designing the future workforce in the shipping industry. Despite a growing interest in new skill development in shipping, limited skill development opportunities remain problematic. The findings highlight the lack of career support systems for seafarers as well as the need for stakeholder engagement in shaping the future maritime skills. Abstract: Industry 4.0 entails the modernisation of work, which is likely to have an impact on individuals' employment, training and skills in the foreseeable future. Current debates on future skills for maritime operations tend to focus on technology as a necessary requirement for workers to adapt to changes. This technology-centred approach can be controversial as technology cannot govern how humans work and how they choose their careers after graduating. This paper employs a career-focused perspective that addresses Industry 4.0 and digitalisation from individuals' career development viewpoint, and discusses the potential implications of digitalisation and automation on individuals' careers in the maritime industry. The paper contributes to the discussion of how Industry 4.0 and digitalisation have the potential to affect individuals' skills and training, as well as their future career trajectories. The paper also scrutinises career structures for seafarers as well as possible socio-economic implications on future maritime careers, skills and training in the context of Industry 4.0. These issues are examined through the use of interview data from two empirical projects between 2007 and 2018 as well as a literature review on careers in the global labour market and on Industry 4.0. It concludes with a set of agendas highlighting potential shortage of career support systems for seafarers as well as the need for stakeholder engagement in shaping future maritime skills.